Evaluating the Cooling Performance of Green Roofs Under Extreme Heat Conditions - Feng, Ye; Wang, Jia; Zhou, Weiqi; Li, Xiaoma; Yu, Xiaoying (Frontiers in Environmental Science, 2022)
The local rise in urban temperature is increasingly exacerbated due to the combined effect of urban heat islands and global climate change. Numerous studies have shown that green roofs (GR) have great potential for facilitating urban heat mitigation. However, little is known about whether such cooling effects can be achieved under extreme heat conditions. With the expected occurrence of more extreme heat events under climate change, such understanding is crucially important for the effective design of heat mitigation. This study aims to fill this gap by investigating the pedestrian-level cooling effect of GR under two kinds of weather conditions (i.e. typical summer weather conditions and extreme heat conditions) and how cooling effect changes with the increase of roof height. This research employed a three-dimensional simulation model, ENVI-met, to simulate pedestrian-level air temperature for three typical residential areas with different roof heights in Beijing. We conducted the simulations in two different roof scenarios, conventional roofs versus green roofs, under two kinds of weather conditions. The results showed that the pedestrian-level cooling intensity of GR ranges between 0.00- 0.02°C under extreme heat conditions, smaller than that of 0.01- 0.04°C under typical summer weather conditions. These temperature reductions varied significantly diurnally following an inverted W-shape for both weather conditions. Results also showed that the pedestrian-level cooling intensity of GR decreased with the increase in roof height in a non-linear way and became 0 when roof height reached ~50m for both weather conditions. Understanding the pedestrian-level cooling effect of green roofs under extreme heat conditions and its change along with roof height can provide important insights for cooling-oriented urban design in the future, as we are expecting such extreme weather conditions nowadays may be the new normal in the future.